Effect of Pr3+/Pr4+ ratio on the oxygen ion transport and thermomechanical properties of the pyrochlore and fluorite phases in the ZrO2–Pr2O3 system. (22nd June 2016) - Shlyakhtina, A.V.; Abrantes, J.C.C.; Gomes, E.; Shchegolikhin, A.N.; Vorobieva, G.A.; Maslakov, K.I.; Knotko, A.V.; Shcherbakova, L.G.
Abstract: This paper examines the effect of the Pr 3+ /Pr 4+ ratio on the mechanism of ionic and electronic transport in the (Pr2−x Zrx )Zr2 O7+x/2 ( x = 0.15), Pr2 Zr2 O7, and Pr2 (Zr2−x Prx )O7−x/2 ( x = 0.1) pyrochlore phases and Pr3 ZrO x with the fluorite structure and on the behavior of their thermal expansion coefficient (TEC). The solid solutions were prepared through coprecipitation followed by firing of the green compacts in air at a high temperature of 1550 °C for 4 h. The Pr 3+ /Pr 4+ ratio was shown to decrease in going from the (Pr2−x Zrx )Zr2 O7+x/2 (x = 0.15), Pr2 Zr2 O7, and Pr2 (Zr2−x Prx )O7−x/2 (x = 0.1) pyrochlores to the Pr3 ZrOx fluorite, leading to changes in the conductivity type from mixed (ionic–electronic) to electronic and in the color of the materials from beige to black and to an anomalous deviation of the TEC from linearity in fluorite Pr3 ZrO x, i.e. at the highest Pr 4+ content. According to impedance spectroscopy results, (Pr2−x Zrx )Zr2 O7+x/2 with x = 0.15 has purely oxide-ion conductivity (3 × 10 −3 S/cm at 1000 °C) in a wide range of oxygen partial pressures: from 10 −10 to 10 2 Pa. With increasing Pr content, p-type electronic conductivity becomes significant, reaching a maximum in fluorite Pr3 ZrO x : ∼0.5 S/cm at 1000 °C. According to XPS data, all pyrochlore samples (Pr2−x Zrx )Zr2 O7+x/2 (x = 0.15), Pr2 Zr2 O7 and Pr2 (Zr2−x Prx )O7−x/2 (x = 0.1) contain only Pr 3+ at room temperature, whereas Pr3 ZrOx contains both Pr 3+ and Pr 4+ . The considerable deviation of the TEC of Pr3 ZrO x from linearity above 500 °C is due to partial reduction of Pr 4+ . The reduction process Pr 4+ + e ′ → Pr 3+ followed by oxygen release in the range 500–1100 °C has been identified in Pr3 ZrO x by thermal analysis and mass spectrometry in a He atmosphere. Highlights: The Pr 3+ /Pr 4+ ratio decreases across the ZrO2 –Pr2 O3 solid solutions series. This leads to changes in the conductivity type from mixed to electronic. (Pr2−x Zrx )Zr2 O7+x/2 ( x = 0.15) is pure oxide-ion conductor (0.03 S/cm at 1000 °C) from 10 −10 to 10 2 Pa. An anomalous deviation of the TEC from linearity was shown by Pr3 ZrOx fluorite. The reduction process of Pr 4+ at the 500–1100 °C has been stated in Pr3 ZrOx .